Amelia jane is naughty again! - Blyton, Enid (Egmont, Great Britain., 1954)
New editions, with new illustrations and new format, of all four Amelia Jane titles. Amelia Jane is big, bad and the terror of the toy cupboard! In this book, Amelia Jane plays all sorts of tricks on the toys. She steals the teddy bear's necklace, causes chaos with a boomerang. Can the toys teach her a lesson?
Keywords: English, Fiction